An Amarna letter (EA 162) from a pharaoh to Aziru of Amurru in light of recent research - Muntingh, L. M. (Journal for semitics, 1995)
By the middle of the second millennium B.C. Akkadian had spread from the homeland Babylonia-Assyria to neighbouring countries in the Near East and Egypt. An offshoot of Akkadian - indicated by scholars as Peripheral Akkadian - became the lingua franca and the vehicle for international diplomacy. It consisted of numerous dialects and subdialects.